ПЕРЕХОДНЫЕ ПРОЦЕССЫ В RLC-ЦЕПЯХ С ПАРАМЕТРИЧЕСКОЙ НАГРУЗКОЙ - Шидловская, Н.А.; Захарченко, С.Н. (Інститут електродинаміки НАН України, Київ, 2014)
The results of the solution of the differential equation which presenting transients in a serial RLC-circuits resistance of its active element is presented by the sum exponential dependences on a time are given. Conditions at which the input equation can be transformed to the equation of Rikkarti are discovered. It is shown a basic possibility of deriving of an exact solution of such equation at certain relations between values of its factors. References 6, figures 3.